Smart Solar Panel Tracking Dual Axis Menggunakan Sensor LDR Berbasis Arduino - Joni Eka Candra; Ririt Dwiputri Permatasari; Zainul Munir; M. Ansyar Bora (LPPM STIKOM Tunas Bangsa, 2023)
Renewable energy is the choice for several reasons, including: it is relatively cheap, carbon neutral, mostly non-polluting and has support from various NGOs to replace energy solutions based on non-renewable fuels. In addition, the application of this technology in rural communities can provide opportunities for rural communities to independently manage and meet their own energy needs and solutions. One form of renewable energy is solar energy. To be able to convert solar energy into electricity, solar panels are needed that can convert solar energy directly into electricity and store it in batteries. The use of solar panels has been widely used in Indonesia, but not optimal. So far, the solar panels used by the community are static, resulting in less than optimal use of solar energy. A statically placed solar panel can only receive a constant maximum of 3 hours of insolation. Therefore, we need a tool that can make dynamic solar panels that can follow the movement of sunlight so that the solar panels receive a constant maximum light for a longer period of time, thereby reducing the cost of purchasing the number of solar panels that can be used. To generate solar energy, dynamic panel movement when the sun moves requires an electronic device as a controller, an example of a controller that can be used is Arduino. From the test results, the design with a dynamic angle of 60˚ solar tracker shows the highest average power of 34.59 W/hour and an average efficiency value of 3.58%. This is compared to testing at an angle of 300 which averages 32.64 watts/hour with an efficiency of 3.33%, and at an angle of 90° which averages 13.03 watts/hour with an efficiency of 1.30%.